Pengembangan Bahan Ajar Gerak Benda Angkasa Menggunakan Four Steps Teaching Material Development - Nadya Meriza; Parlindungan Sinaga; Nur Inayah Syar (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
This study applied Four Steps Teaching Material Development to develop an integrated science teaching material theme space object movement and found out the effect of its implementation to enhance scienctific literacy. This study used R n D methode, while nonequivalent pretest and postest control group design used in the implementation then. The sampling of this study was eight grader at one of junior high school in Bandung. The result revealed that integrated science teaching material developed get into good categorize by percentage amount 70%. The implementation of integrated science teaching material developed increasing scientific literacy significantly compared to science teaching material from another source. Increasing science literacy the experimental group was higher than the control group with a value range of 17%. Futhermore integrated science teaching material is suitable to use during learning process. Tujuan penelitian untuk menganalisis pengembangan bahan ajar IPA Terpadu terhadap peningkatan kemampuan literasi sains siswa. Metode penelitian ini adalah Research and Development dan menggunakan desain Nonequivalent Pretest and Postest Control Group Design. Sampel penelitian ini adalah siswa kelas VIII salah satu sekolah di Kota Bandung. Hasil penelitian menunjukkan bahwa bahan ajar IPA Terpadu yang dikembangkan termasuk ke dalam kategori baik dengan persentase sebesar 70%. Implementasi bahan ajar IPA Terpadu dapat meningkatkan literasi sains siswa lebih baik dibandingkan dengan bahan ajar dari sumber lain. Peningkatan kemampuan literasi pada kelompok eksperimen lebih tinggi dibandingkan kelompok kontrol dengan rentang nilai sebesar 17%. Berdasarkan hasil analisis disimpulkan bahwa bahan ajar IPA Terpadu yang dikembangkan layak digunakan sebagai bahan ajar pendamping dalam pembelajaran IPA. Kata kunci: bahan ajar, IPA Terpadu, four steps teaching material development, literasi sains